2010
DOI: 10.1093/mutage/geq047
|View full text |Cite
|
Sign up to set email alerts
|

Genetic damage in chronic renal failure patients is associated with the glomerular filtration rate index

Abstract: Chronic renal failure (CRF) patients are considered to present genomic instability and, as a consequence, elevated levels of genetic damage. An open question is whether this damage is related to the stage of the pathology. To determine the background levels of genetic damage, a large population of 258 Caucasian adults (201 CRF patients and 57 controls) was analysed using the micronucleus (MN) assay. The frequency of MN in CRF patients was significantly higher than in controls and correlated with the progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…This agrees with Stopper et al (5), who found that in comparison with healthy controls, MN in PBL is increased approximately 2-fold in pre-dialysis CKD patients. Our study concurs with results in previous studies showing increased cytogenetic effects with regards to MN frequencies in pre-dialysis CKD and in patients with a different modality of dialysis treatment (5,14,39–41). …”
Section: Discussionsupporting
confidence: 93%
“…This agrees with Stopper et al (5), who found that in comparison with healthy controls, MN in PBL is increased approximately 2-fold in pre-dialysis CKD patients. Our study concurs with results in previous studies showing increased cytogenetic effects with regards to MN frequencies in pre-dialysis CKD and in patients with a different modality of dialysis treatment (5,14,39–41). …”
Section: Discussionsupporting
confidence: 93%
“…In patients with ESRD, genomic damage has been shown by numerous biomarkers, such as the analysis of sister chromatid exchange and chromosomal aberrations (Cengiz et al, 1988, Lialiaris et al, 2010, MN frequency (Stopper et al, 1999;Sandoval et al, 2010), comet assay in peripheral lymphocytes (Stopper et al, 2001;Kobras et al, 2006;Aykanat et al, 2011), 8-hydroxy 2-deoxyguanosine content in leukocytes (Tarng et al, 2004), and mitochondrial DNA deletions in skeletal muscle tissue and hair follicles (Liu et al, 2001). Our results also confirmed that patients with ESRD exhibit increased levels of genomic damage, as measured by the MN assay.…”
Section: Discussionsupporting
confidence: 82%
“…In the literature, there are a few previous studies using the MN assay in peripheral blood lymphocytes of patients with chronic renal failure (Stopper et al, 1999;Kobras et al, 2006;Schupp et al, 2008;Sandoval et al, 2010). All of them show increased MN levels in patients with chronic renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…The biomarkers used in these studies were micronuclei in peripheral blood lymphocytes (PBL) (7,(25)(26)(27) and BEC (9), chromosome aberrations and sister chromatid exchanges (28,29), and DNA strand breaks (comet assay) (26-28, 30, 31). The only reports regarding children with CKD were our recent studies using the MN and comet assays in PBL of children (15,16).…”
Section: Resultsmentioning
confidence: 99%